2020
DOI: 10.1088/1402-4896/abcd67
|View full text |Cite
|
Sign up to set email alerts
|

Noether symmetry approach in energy-momentum squared gravity

Abstract: In this paper, we investigate the newly developed f (R, T 2 ) theory (R is the Ricci scalar and T 2 = T αβ T αβ , T αβ demonstrates the energymomentum tensor) to explore some viable cosmological models. For this purpose, we use the Noether symmetry approach in the context of flat Friedmann-Robertson-Walker (FRW) universe. We solve the Noether equations of this modified theory for two types of models and obtain the symmetry generators as well as corresponding conserved quantities. We also evaluate exact solutio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…We have examined some physically viable solutions through the Noether symmetry strategy in this framework. [ 34 ] We have also discussed the dynamics of celestial objects and found that collapse rate reduces in EMSG as compared to GR. [ 35 ] The physical features of a gravastar in this framework has been studied in [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…We have examined some physically viable solutions through the Noether symmetry strategy in this framework. [ 34 ] We have also discussed the dynamics of celestial objects and found that collapse rate reduces in EMSG as compared to GR. [ 35 ] The physical features of a gravastar in this framework has been studied in [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The viability of isotropic cosmos has also been analyzed in this theory by using flat FLRW metric [47]. Sharif and Gul [48] constructed various cosmological as well as astrophysical solutions via different techniques and discussed their viability and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Bahamonde et al [11] presented the expansion of cosmos using different coupling models and found that these models are a good fit to explain the current behavior of cosmos. Sharif and Gul [12] used Noether symmetries in this theory and studied the impact of different physical parameters on viable cosmological structures. They also inspected the viability as well as stability of compact celestial bodies and concluded that the correction terms of the gravity decrease the collapse.…”
Section: Introductionmentioning
confidence: 99%